2022
DOI: 10.1186/s12889-022-13188-8
|View full text |Cite
|
Sign up to set email alerts
|

The political determinants of the health of undocumented immigrants: a comparative analysis of mortality patterns in Switzerland

Abstract: Background The health of undocumented immigrants is an important concern in most societies. However, there is no conclusive evidence that inclusive health care policies lead to better outcomes for this group of the population. The aim of this study is to analyse whether there is an association between inclusive health care policies and the mortality patterns of undocumented immigrants, or the distribution of different causes of death among those who have died. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In their systematic analysis, Vernice et al (2020) showed that mental health is linked to the configuration of immigration policies and whether access to healthcare is possible. Similarly, Piccoli and Wanner (2022) , emphasized that health of undocumented migrants differs between Swiss cantons depending on the level of inclusiveness of health policies. Our findings allow to nuance and point to the importance of taking stressors away from undocumented migrants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their systematic analysis, Vernice et al (2020) showed that mental health is linked to the configuration of immigration policies and whether access to healthcare is possible. Similarly, Piccoli and Wanner (2022) , emphasized that health of undocumented migrants differs between Swiss cantons depending on the level of inclusiveness of health policies. Our findings allow to nuance and point to the importance of taking stressors away from undocumented migrants.…”
Section: Discussionmentioning
confidence: 99%
“…Poorer self-reported health among undocumented migrants is associated with hardworking conditions, limited social interaction as well as precarious living conditions ( Ahonen et al, 2009 ; Fakhoury et al, 2021 ; Jolivet et al, 2012 ; Kumparatana et al, 2017 ; Pikhart et al, 2010 ; Sousa et al, 2010 ; Woodward et al, 2014 ). This could explain the higher mortality rates among undocumented migrants recently reported in Switzerland ( Piccoli & Wanner, 2022 ). However, scholars showed that the difference in health evaluations is not primarily due to the acquisition of a residence status, but results from better healthcare and socioeconomic opportunities once documented ( Cloos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 92%
“…These health policy differences reflect variation in other non-health policies targeting undocumented migrants and may contribute to the gradient in undocumented migrants' mortality across cantons. 17 As a Federal State with completely decentralized health system governance, regional COVID-19 response policy varied widely. Only few cantons adopted a proactive and inclusive strategy to alleviate financial and administrative barriers to testing, treatment, and vaccination for uninsured migrants.…”
Section: The Covid-19 Pandemic Response: Analysis Through Country Cas...mentioning
confidence: 99%
“…Barriers to accessing health services are of particular concern in the case of undocumented migrants because past experiences and current situations often increase their susceptibility to disease and vulnerability to a range of health threats. These may arise from their living conditions, which may be overcrowded and lacking adequate sanitary facilities; from food insecurity, reliance on public transportation for mobility, absence of locally accessible medical services, communication barriers between physicians and im-migrant patients that limit access to health information and services (including key messages on COVID-19 prevention and health-seeking behaviour), and digital illiteracy and/or communication barriers that limit access to telemedicine [ 9 , 10 , 11 , 12 ]. Moreover, environmental factors, such as long-term average exposure to fine particulate matter having a diameter of less than 2.5 μm (PM2.5), may also influence COVID-19 outcomes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%